Contemporary Advertising In Islamic Perspective - Arief Fadhillah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
This paper purposes to examine the principles and implementation of contemporary advertising in an Islamic perspective. The research employs the method of literature study, by examining the perspective of Islamic advertising from various research literatures, the opinions of scholars and the Qur'an and Hadith. Based on literature review, the development of advertising is still trapped in the practice of materialistic advertising that overrides the ethics of Islamic communication. For this reason, this study formulates six advertising principles referring to the Qur'an and Hadith as well as the opinions of scholars, namely the principle of monotheism, the principle of honesty, the principle of justice, the principle of trust, the principle of education and the principle of Istiqomah/consistent. This study can be developed by referring to technological developments and the need for communication and religious research in the future.